PENGARUH SUBSTITUSI BONGGOL PISANG TERHADAP KUALITAS KERUPUK IKAN TENGGIRI - Martines, Silvia; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research is motivated by the utilization of banana cobs that have not varied and the price of mackerel fish is expensive. This study aims to analyze the effect of substitution of banana stumps by 0%, 25%, 50% and 75% on the quality of mackerel fish tuna in terms of uniform and tidy shapes, color, aroma, taste and texture. The type of this study was pure experiment using a complete randomized design method of three repetitions. Types of data used are primary data sourced from 30 panelists who provide answers from questionnaires (organoleptic test format). The data that have been obtained is tabulated and analyzed by variant (ANAVA). If different proceed with Duncan test. The results showed that there was significant effect on the quality of mackerel fish crackers on the quality of brownish white color, savory taste, fragrant aroma but no effect on the quality of form uniformity, neat shape, and crunchy texture. It can be concluded that the best percentage is in the substitution of 25% of banana cobs.Keywords :Banana Stalks, Mackerel Fish Crackers,Quality.